Urban–rural differences in mental health among Chinese patients with multiple chronic conditions. (14th October 2019) - Cheng, Cheng; Yang, Cong‐Yan; Inder, Kerry; Wai‐Chi Chan, Sally
Abstract: Mental health is impacted by social, economic, and environmental influences related to where people live. Mental health problems commonly co‐occur with long‐term physical conditions and impact individuals' health synergistically. Multiple chronic conditions (MCCs) including mental health problems are becoming a public health challenge globally. However, there is limited information about urban–rural differences in mental health among patients with MCCs in China. The present study aimed to identify differences in mental health between urban and rural patients with MCCs. Using a cross‐sectional design, 347 patients with MCCs were recruited from a tertiary hospital in North Anhui, China. A self‐reported questionnaire, including socio‐demographic and clinical variables, the 12‐item Short‐Form survey version 2 on quality of life, and the Hospital Anxiety and Depression Scale, was administered to outpatients. Findings showed that rural participants reported more symptoms of anxiety and depression and had worse mental health compared to urban participants. Unemployment status, lower educational level, more long‐term health conditions, and a higher degree of anxiety were associated with worse mental health. This study highlights disparities in mental health among patients with MCCs living in urban and rural areas of China. Appropriate mental health support programmes should be developed for patients with MCCs, especially for those living in rural areas.